Association between homocysteine levels and hyperlipidemia prevalence as well as all-cause mortality of hyperlipidemia patients in the US population: results from NHANES database - Wei, Jia; Yang, Qiang; Wang, Xiaofang; He, Xin; Zhu, Wenjing; Lin, Lin; Liu, Chang; Zhu, Canzhan; Zhang, Mingjuan (Frontiers in Cardiovascular Medicine, 2024)
Several studies have investigated the correlation between blood lipids and homocysteine, but no clear conclusions have been defined yet. Therefore, we utilized data from National Health and Nutrition Examination Survey (NHANES) to explore the correlation between serum homocysteine (Hcy) levels and hyperlipidemia, which is determined by the levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG).We believe this study can provide a scientific basis for the prevention and treatment of lipid abnormalities.